Sets technology to boost onion production in Ladakh - Singh, Narendra; Arya, Jagdish Singh (Indian Horticulture, 2019)
The production and productivity of onion can be increased manifold in Ladakh by adopting â€œSets Technologyâ€ by the farmers. The requirement of civil population and the army can be met easily. Subsequently, farmers can earn substantial money with increased yield per unit area of onion crop.